ENTRE NÚMEROS E PALAVRAS: DIFERENÇAS QUE COLIDEM NO FRACASSO ESCOLAR - Rodrigues, Isabel Cristina dos Santos (2015)
This dissertation - Between numbers and words: differences collide in school failure - looking first observe the curriculum guidelines and evaluation systems, with emphasis on the Official Curriculum, established in 2008, and the School Performance Evaluation System (SARESP) the State of São Paulo, to then seek to understand the relationships established when observed by the speech of teachers, which in the classroom are the point of contact between the curriculum and the students. For both, beyond the analysis of curriculum documents and official evaluation systems, countersign us on theoretical assumptions related to curriculum field, the main bias the concepts of cultural capital and habitus developed by Pierre Bourdieu. From these discussions and concepts are organized interviews with Portuguese teachers of 9th grade of elementary education in public schools of São Paulo, in which we seek to problematize the Official Curriculum, targets and performance results established by SARESP, the power relations and ideology present in the curriculum guidelines at the meeting with the religious cult Capital of students. So, this study observed a wide range of practices that mobilize the educational, with reflections on the school run, as well as teachers and students; and then questions the establishment of curriculum guidelines, the establishment of official curricula and its uniqueness, the results from systemic reviews, power relations and ideologies that cross the official documents and their influence on the schooling of students.